(untitled) (Global Journals of Research in Engineering, 2022)
In wind energy conversion system extraction of optimum power and efficient operation are two major challenges In grid connected mode a doubly fed induction generator DFIG control unit is designed to operate at optimum speed to deliver maximum output power in the grid while the voltage frequency and harmonic regulations need to be fulfilled Vector control associated with proportional-integral PI controllers has been widely applied in wind farms for reliable power regulation of DFIG As DFIG based wind energy conversion system WECS experiences strong nonlinearity and uncertainties originated from the aerodynamics of the wind turbine and magnetic saturation of the generator different adaptive and nonlinear control schemes have been proposed to resolve the problems associated with fixed-gain PI controllers Among adaptive controllers adaptive fuzzy inference system AFIS has the distinguishing feature of modeling a highly nonlinear system and adopting the uncertainties Hence in this paper an AFIS based NFC controller is proposed to regulate the converters of gridconnected DFIG The proposed algorithm is tested for variable wind speed conditions and the results are compared with fixed gain PI controller and adaptive back-stepping based nonlinear controller The simulation results suggest that the proposed scheme shows excellent adaptation with the variable condition through the change of its parameters and comparatively better performance in terms of speed and current tracking